Thymoquinone overcomes chemoresistance and enhances the anticancer effects of bortezomib through abrogation of NF-κB regulated gene products in multiple myeloma xenograft mouse model - Siveen, K.; Mustafa, N.; Li, F.; Kannaiyan, R.; Ahn, K.; Kumar, Alan Prem; Chng, W.; Sethi, G. (Impact Journals LLC, 2014)
Multiple myeloma (MM) is a B cell malignancy characterized by clonal proliferation of plasma cells in the bone marrow. With the advent of novel targeted agents, the median survival rate has increased to 5 -7 years. However, majority of patients with myeloma suffer relapse or develop chemoresistance to existing therapeutic agents. Thus, there is a need to develop novel alternative therapies for the treatment of MM. Thus in the present study, we investigated whether thymoquinone (TQ), a bioactive constituent of black seed oil, could suppress the proliferation and induce chemosensitization in human myeloma cells and xenograft mouse model. Our results show that TQ inhibited the proliferation of MM cells irrespective of their sensitivity to doxorubicin, melphalan or bortezomib. Interestingly, TQ treatment also resulted in a significant inhibition in the proliferation of CD138+ cells isolated from MM patient samples in a concentration dependent manner. TQ also potentiated the apoptotic effects of bortezomib in various MM cell lines through the activation of caspase-3, resulting in the cleavage of PARP. TQ treatment also inhibited chemotaxis and invasion induced by CXCL12 in MM cells. Furthermore, in a xenograft mouse model, TQ potentiated the antitumor effects of bortezomib (p < 0.05, vehicle versus bortezomib + TQ; p < 0.05, bortezomib versus bortezomib + TQ), and this correlated with modulation of various markers for survival and angiogenesis, such as Ki-67, vascular endothelial growth factor (VEGF), Bcl-2 and p65 expression. Overall, our results demonstrate that TQ can enhance the anticancer activity of bortezomib in vitro and in vivo and may have a substantial potential in the treatment of MM.